Implikasi Undang-Undang Penyiaran Terhadap Pertumbuhan Lembaga Penyiaran di Propinsi Kepulauan Riau - Azwardi Azwardi (Journal of Law and Policy Transformation, 2020)
The growth of broadcasting stations (LP) studied in this thesis is the growth of existing station in Riau Islands Province (Kepri) after officially established of Law Republic of Indonesia Number 32 of 2002 concerning Broadcasting, which in the broadcast legislation looks more leads to liberalism is loaded with privatization that provides opportunities for offenders efforts to expand its business in the broadcasting industry, including in the Kepri. Legal theories used by researchers is a critical legal theory and legal theory flow Critical Legal studies(CLS). This study was conducted to showed that law Broadcasting Act, Article 13 paragraph (1) and (2) has been split into Public Broadcasting Stations (LPP), Private Broadcasting Stations (LPS), Community Broadcasting Stations (LPK) and Subscription Broadcasting Station (LPB). Base to The Indonesian Broadcasting Commission (KPI) of Kepri, the numbers of broadcasting stations listed till 2014 (television and radio services) is 0 LPP, 55 LPS, 23 LPB and 2 LPK. Of these known 69% of the total number of LP in Kepri is LPS. According to critical theory, democracy has influenced the policy direction of the holders of power (broadcasting law) to the interests of capital, and this is in line with the flow of Critical Legal Studies, which states that all regulations set by the government is closely linked to the ideology espoused by the government, so this theory argues that the legal and political (broadcasting legislation) are not in the neutral position. For the current broadcasters to benefit from more focused on improving the public thinks.